Crystals and their manufacturing method
Patent Information
- Application Number
- JP2021565668
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2019-12-20
- Filing Date
- 2020-12-18
- Publication Date
- 2025-03-05
- Estimated Expiration
- 2040-12-18
AI Technical Summary
【0010】 本発明によれば、新規な結晶[新規な3-ヒドロキシ-N’-(1,3-ジメチルブチリデン)-2-ナフトエ酸ヒドラジドの結晶]を提供できる。
Smart Images

Figure 0007640470000004 
Figure 0007640470000005 
Figure 0007640470000001
Abstract
Description
[Technical field]
[0001] The present invention relates to novel crystals and the like. [Background technology]
[0002] 2. Description of the Related Art Various additives are used in rubber products such as tires. For example, hydrazide compounds are used as rubber additives (Patent Document 1, etc.). [Prior art documents] [Patent documents]
[0003] [Patent Document 1] JP 2019-6845 A Summary of the Invention [Problem to be solved by the invention]
[0004] An object of the present invention is to provide a novel crystal.
[0005] Another object of the present invention is to provide a method for producing a novel crystal.
[0006] Another object of the present invention is to provide a novel rubber additive. [Means for solving the problem]
[0007] As a result of intensive research aimed at solving the above problems, the present inventors focused on 3-hydroxy-N'-(1,3-dimethylbutylidene)-2-naphthoic acid hydrazide and found that novel crystals of the compound can be obtained by appropriately selecting conditions for precipitating (i.e., crystallizing) the crystals.
[0008] Furthermore, the present inventors have found that among the novel crystals, each crystal imparts different physical properties to a rubber component when used as a rubber additive. Furthermore, they found that the first crystal of the present invention is superior to the second crystal of the present invention in terms of low heat generation, and that the second crystal is superior to the first crystal in terms of processability, and after further intensive research, they have completed the present invention.
[0009] That is, the present invention relates to the following inventions. [1] A crystal of 3-hydroxy-N'-(1,3-dimethylbutylidene)-2-naphthoic acid hydrazide having a peak with maximum intensity at a diffraction angle (2θ) of 6.9±0.2° in a powder X-ray diffraction pattern. [2] A crystal of 3-hydroxy-N'-(1,3-dimethylbutylidene)-2-naphthoic acid hydrazide having characteristic peaks at diffraction angles (2θ) of at least 6.9±0.2°, 14.5±0.2°, 15.5±0.2°, 19.1±0.2°, 23.4±0.2°, 24.1±0.2°, 27.9±0.2°, and 28.8±0.2° in a powder X-ray diffraction pattern. [3] A crystal of 3-hydroxy-N'-(1,3-dimethylbutylidene)-2-naphthoic acid hydrazide having a peak of maximum intensity at a diffraction angle (2θ) of 11.4±0.2° and / or 25.2±0.2° in a powder X-ray diffraction pattern. [4] A crystal of 3-hydroxy-N'-(1,3-dimethylbutylidene)-2-naphthoic acid hydrazide having characteristic peaks at diffraction angles (2θ) of at least 11.2±0.2°, 11.4±0.2°, 13.5±0.2°, 15.5±0.2°, 15.8±0.2°, 16.3±0.2°, 18.4±0.2°, 21.6±0.2°, 22.0±0.2°, 25.2±0.2°, and 26.3±0.2° in a powder X-ray diffraction pattern. [5] A crystal comprising the crystal according to [1] or [2] above and the crystal according to [3] or [4] above. [6] The crystal according to the above [5], wherein the ratio of the peak intensity at a diffraction angle (2θ) of 11.4±0.2° to the peak intensity at a diffraction angle (2θ) of 6.9±0.2° is 1:99 to 10:90. [7] The crystal according to any one of the above [1] to [6], which has a melting point of 151° C. or higher. [8] A rubber additive comprising the crystals according to any one of the above [1] to [7]. [9] A rubber composition comprising the rubber additive according to [8].
[10] A tire using the rubber composition according to [9] above.
[11] A method for producing the crystal according to the above [1] or [2], comprising at least a step of forming crystal nuclei at 50° C. or higher in a solution containing 3-hydroxy-N'-(1,3-dimethylbutylidene)-2-naphthoic acid hydrazide.
[12] The method according to [3] or [4] above, further comprising at least a step of precipitating crystals from a solution of 3-hydroxy-N'-(1,3-dimethylbutylidene)-2-naphthoic acid hydrazide dissolved in a solvent containing methanol and methyl isobutyl ketone.
[13] A method for improving low heat build-up and / or processability of rubber, using the crystals according to any one of the above items [1] to [7].
[14] Use of the crystal according to any one of the above [1] to [7] for improving low heat build-up and / or processability of rubber. Effect of the Invention
[0010] According to the present invention, a novel crystal (a novel crystal of 3-hydroxy-N'-(1,3-dimethylbutylidene)-2-naphthoic acid hydrazide) can be provided.
[0011] Moreover, the present invention can provide a novel rubber additive containing the above crystals. Such rubber additives can impart low heat generation properties to the rubber component, and when used in a rubber composition, can provide a rubber product (such as a tire) that exhibits low heat generation properties.
[0012] Generally, when attempting to impart low heat generation properties to a rubber component, processability tends to decrease, but the rubber additive of the present invention can achieve both low heat generation and processability.
[0013] The present invention also provides a novel method for producing crystals. [Brief description of the drawings]
[0014] [Figure 1] 1 shows the results of powder X-ray diffraction measurement of the crystals of Example 1. [Diagram 2] 1 shows the results of powder X-ray diffraction measurement of the crystals of Example 2. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0015] [crystal] (Crystal A) The first crystal (Crystal A) of 3-hydroxy-N'-(1,3-dimethylbutylidene)-2-naphthoic acid hydrazide of the present invention will be described. Crystal A may have a peak of maximum intensity at a diffraction angle (2θ) of, for example, 6.9° in a powder X-ray diffraction pattern analyzed by a powder X-ray diffractometer using Cu-Kα radiation (wavelength λ=1.54 Å).
[0016] In addition, crystalline A may have characteristic peaks at diffraction angles (2θ) of at least 6.9°, 14.5°, 15.5°, 19.1°, 23.4°, 24.1°, 27.9°, and 28.8° in a powder X-ray diffraction pattern analyzed with a powder X-ray diffractometer using Cu-Kα radiation (wavelength λ=1.54 Å).
[0017] In addition, in a powder X-ray diffraction pattern analyzed by a powder X-ray diffractometer using Cu-Kα radiation (wavelength λ=1.54 Å), crystalline A may have characteristic peaks at diffraction angles (2θ), such as 6.9°, 14.5°, 15.5°, 16.1°, 19.1°, 23.4°, 24.1°, 27.9°, and 28.8°.
[0018] Generally, the diffraction angle (2θ) in powder X-ray diffraction may vary slightly depending on the measurement conditions, so the crystals of 3-hydroxy-N'-(1,3-dimethylbutylidene)-2-naphthoic acid hydrazide of the present invention also include crystals whose diffraction angles in powder X-ray diffraction match within the error range. The error of the diffraction angle may be, for example, ±0.2°. In other words, the crystals of the present invention also include those whose diffraction angles match within the range of ±0.2° of the above-mentioned diffraction angles. In this specification, "diffraction angle 2θ±0.2°" means a diffraction angle within the range of (2θ-0.2°)≦2θ≦(2θ+0.2°), that is, within the range of (2θ-0.2°) to (2θ+0.2°). In addition, when two peak regions overlap, the two peaks may overlap. For example, the peak at 17.7° and the peak at 17.9° overlap in the peak region in the range of 17.7° to 17.9° in the range of "2θ±0.2°", but the two peaks may exist or overlap within the range of 17.7° to 17.9°.
[0019] Furthermore, when the peak intensity of Crystal A at a diffraction angle (2θ) of 6.9° is taken as 100%, the peak intensity at a diffraction angle (2θ) of 14.5° may be, for example, 22 to 75%, preferably 34 to 69%.
[0020] The peak intensity itself may be different from that described above.
[0021] The melting point of Crystal A exhibits an endothermic peak at 151° C. or higher, preferably 155 to 159° C., and more preferably 156 to 158° C., in differential scanning calorimetry (DSC).
[0022] The form of Crystal A is not particularly limited, and may be an aggregate or a pulverized product obtained by appropriate pulverization.
[0023] The average particle size of the crystal A is not particularly limited, but is preferably the particle size at 50% of the cumulative value calculated by the number conversion method (average particle size D 50 ) may be, for example, 2 μm or more, preferably 5 to 90 μm, and more preferably 6 to 20 μm. When the crystals are aggregates, the size may be adjusted to fall within the above range by an appropriate operation such as pulverization.
[0024] In the present invention, the average particle size D 50 The method for measuring is not particularly limited, and may be, for example, the method described in the Examples below.
[0025] The specific surface area of the crystal A is not particularly limited, but is, for example, 0.2 to 5 m 2 / g, preferably 0.2 to 3 m 2 / g, more preferably 0.4 to 2m 2 / g.
[0026] In the present invention, the method for measuring the specific surface area is not particularly limited, and may be, for example, the method described in the Examples below.
[0027] The shape of the crystal A is not particularly limited and may be, for example, plate-like, columnar, needle-like, etc., and is preferably columnar.
[0028] (Crystal B) Next, the second crystal (Crystal B) of 3-hydroxy-N'-(1,3-dimethylbutylidene)-2-naphthoic acid hydrazide of the present invention will be described. Crystal B may have a peak of maximum intensity at a diffraction angle (2θ), for example, 11.4° and / or 25.2°, in a powder X-ray diffraction pattern analyzed by a powder X-ray diffractometer using Cu-Kα radiation (wavelength λ=1.54 Å).
[0029] In addition, crystalline B may have characteristic peaks at diffraction angles (2θ) of at least 11.2°, 11.4°, 13.5°, 15.5°, 15.8°, 16.3°, 18.4°, 21.6°, 22.0°, 25.2°, and 26.3° in a powder X-ray diffraction pattern analyzed with a powder X-ray diffractometer using Cu-Kα radiation (wavelength λ=1.54 Å).
[0030] In addition, in a powder X-ray diffraction pattern analyzed by a powder X-ray diffractometer using Cu-Kα radiation (wavelength λ=1.54 Å), crystalline B may have characteristic peaks at diffraction angles (2θ), such as 11.2°, 11.4°, 13.5°, 15.5°, 15.8°, 16.3°, 17.2°, 18.4°, 21.6°, 22.0°, 25.2°, 26.3°, and 29.1°.
[0031] Furthermore, when the peak intensity of crystal B at a diffraction angle (2θ) of 11.4° is taken as 100%, the peak intensity at a diffraction angle (2θ) of 13.5° may be, for example, 10 to 87%.
[0032] The melting point of Crystal B exhibits an endothermic peak at, for example, 151° C. or higher, preferably 151 to 162° C., in differential scanning calorimetry (DSC).
[0033] The form of Crystal B is not particularly limited, and may be an aggregate or a pulverized product obtained by appropriate pulverization.
[0034] The average particle size of the crystals B is not particularly limited, but is preferably the particle size at 50% of the cumulative value calculated by the number conversion method (average particle size D 50 ) may be, for example, 0.5 μm or more, preferably 1 to 50 μm, and more preferably 2 to 20 μm. When the crystals are aggregates, the size may be adjusted to fall within the above range by an appropriate operation such as pulverization.
[0035] The specific surface area of the crystal B is not particularly limited, but is, for example, 0.2 to 15 m 2 / g, preferably 0.5 to 10m 2 / g, more preferably 0.9 to 9m 2 / g.
[0036] The shape of the crystal B is not particularly limited and may be, for example, plate-like, columnar, needle-like, etc., and may be preferably columnar.
[0037] The crystal of the present invention may contain both Crystal A and Crystal B. In such a crystal, the ratio of the peak intensity at a diffraction angle (2θ) of 11.4° to the peak intensity at a diffraction angle (2θ) of 6.9° is, for example, 1:99 to 99:1, and may be 5:95 to 95:5, 10:90 to 90:10, 15 to 85 to 85:15, 20:80 to 80:20, 25:75 to 75:25, 30:70 to 70:30, 35:65 to 65:35, 40:60 to 60:40, or the like. In particular, such crystals may have a high content of crystal A, and the ratio of the peak intensity at a diffraction angle (2θ) of 11.4° to the peak intensity at a diffraction angle (2θ) of 6.9° may be, for example, 1:99 to 30:70, preferably 1:99 to 20:80, and more preferably 1:99 to 10:90.
[0038] Furthermore, the crystal of the present invention may include other crystals (other crystal polymorphs) of 3-hydroxy-N'-(1,3-dimethylbutylidene)-2-naphthoic acid hydrazide within the scope of the present invention.
[0039] [Manufacturing method] (Production method of crystal A) The present invention also encompasses a method for producing crystals of compound (1), which comprises at least a step of forming crystal nuclei at 50°C or higher in a solution (hereinafter sometimes simply referred to as "solution A of compound (1)") containing 3-hydroxy-N'-(1,3-dimethylbutylidene)-2-naphthoic acid hydrazide (hereinafter sometimes simply referred to as "compound (1)"). By such a production method, the above-mentioned crystalline form A can usually be produced efficiently and selectively as a crystalline form of compound (1).
[0040] Solution A of compound (1) may be a solution in which compound (1) is dissolved in a solvent, and may be a reaction solution in which compound (1) is produced. The solvent for dissolving compound (1) is not particularly limited, and examples thereof include methyl isobutyl ketone, alcohols (e.g., isopropyl alcohol, butanol, etc.), hydrocarbons (e.g., hexane, heptane, cyclohexane, toluene, benzene, etc.), ethers (e.g., tetrahydrofuran, etc.), esters (e.g., ethyl acetate, butyl acetate, etc.), and the like, which may be used alone or in combination of two or more.
[0041] The reaction liquid used to produce compound (1) may be, for example, a reaction liquid used to produce compound (1) from 3-hydroxy-2-naphthoic acid hydrazide and methyl isobutyl ketone, which are the raw materials for compound (1). As the solvent to be used in the reaction, the above-mentioned solvents for dissolving the compound (1) can be mentioned, but it is preferable to use methyl isobutyl ketone, which is a reaction raw material, as the solvent.
[0042] The concentration of compound (1) in solution A of compound (1) may be, for example, 20% by mass or more, preferably 25% by mass or more, and more preferably 30% by mass or more, from the viewpoint of efficiently obtaining crystals. The concentration of compound (1) in solution A of compound (1) may be, for example, 40% by mass or less, preferably 38% by mass or less, and more preferably 35% by mass or less, from the viewpoint of efficiently obtaining crystals.
[0043] Furthermore, when solution A of compound (1) is a reaction liquid obtained by reacting 3-hydroxy-2-naphthoic acid hydrazide with methyl isobutyl ketone, the concentration of 3-hydroxy-2-naphthoic acid hydrazide in the solution for obtaining the reaction liquid may be, for example, 15% by mass or more, preferably 19% by mass or more, and more preferably 23% by mass or more, from the viewpoint of efficiently obtaining crystals. The concentration of 3-hydroxy-2-naphthoic acid hydrazide in the solution for obtaining the reaction solution may be, for example, 32% by mass or less, preferably 30% by mass or less, and more preferably 28% by mass or less, from the viewpoint of efficiently obtaining crystals.
[0044] Solution A of compound (1) can be prepared, for example, by heating a solution containing compound (1). The heating temperature can be appropriately selected depending on the type of solvent, and is not particularly limited as long as it is a temperature at which compound (1) dissolves in the solvent. For example, the heating temperature is 70°C or higher, preferably 75°C or higher, more preferably 80°C or higher, and may be 100°C or higher, 110°C or higher, 115°C or higher, etc. The reaction for producing compound (1) from 3-hydroxy-2-naphthoic acid hydrazide and methyl isobutyl ketone is carried out under heating conditions, and therefore the reaction solution can be used as it is as solution A of compound (1). In particular, when the solvent for the reaction is methyl isobutyl ketone, it is suitable as solution A of compound (1) because it is heated to 110° C. or higher. The heating operation may be performed for any period of time as long as the compound (1) is completely dissolved.
[0045] The nucleation step is usually a step of forming crystal nuclei of compound (1) at 50° C. or higher. The nucleation step may be carried out by cooling solution A of compound (1). The cooling rate is not particularly limited, but from the viewpoint of efficiently obtaining crystal nuclei, it may be, for example, 0.5 to 30° C. / min, preferably 0.5 to 20° C. / min, and more preferably 0.5 to 10° C. / min.
[0046] The cooling temperature varies depending on the type of solvent used and the concentration of compound (1), but is usually 50° C. or higher, preferably 55° C. or higher, and more preferably 60° C. or higher. In order to efficiently obtain crystal nuclei, the cooling temperature is preferably 90° C. or lower, and more preferably 85° C. or lower. The nucleation step is preferably carried out so that the solution A of compound (1) does not come into contact with oxygen, and more preferably under an atmosphere of an inert gas such as nitrogen.
[0047] After the crystal nuclei of compound (1) are formed, the crystals may be further precipitated in the same temperature range, but it is preferable to provide a crystallization step in which the crystallization is caused by rapid cooling. The cooling rate in the crystallization step is not particularly limited, but from the viewpoint of efficiently obtaining crystals, it may be, for example, 0.5 to 30° C. / min, preferably 0.5 to 20° C. / min, and more preferably 0.5 to 10° C. / min. The cooling temperature in the crystallization step is not particularly limited, and may be, for example, 30° C. or lower, preferably 15° C. or lower, and more preferably 10° C. or lower.
[0048] In the crystallization step, aging may be carried out at the cooling temperature. The aging time may be, for example, 0.1 minute to 3 hours, preferably 1 minute to 1 hour, and more preferably 5 to 30 minutes. The maturation may be, for example, a procedure of stirring or leaving the solution A of compound (1) without adding any other components.
[0049] The crystallization may be carried out by adding previously prepared crystals of compound (1) as seed crystals. The seed crystals may be prepared using the production method of the present invention.
[0050] The proportion of seed crystals added is not particularly limited, and may be 10% by mass or less (for example, 0.05 to 10% by mass, 0.1 to 8% by mass, 0.1 to 5% by mass) of the substrate (compound (1)).
[0051] (Production method of Crystal B) The present invention also encompasses a method for producing crystals of compound (1), which comprises at least a step of precipitating crystals from a solution of compound (1) dissolved in a solvent containing methanol and methyl isobutyl ketone (hereinafter, sometimes simply referred to as "solution B of compound (1)"). By such a production method, the above-mentioned crystal B can usually be produced efficiently and selectively as a crystal of compound (1). The solvent may contain a solvent other than methanol and methyl isobutyl ketone.
[0052] In the solvent used for solution B of compound (1), the content ratio of methanol and methyl isobutyl ketone is not particularly limited. From the viewpoint of efficiently obtaining crystals, the mass ratio of methanol:methyl isobutyl ketone may be, for example, 95:5 to 10:90, preferably 90:10 to 30:70, and more preferably 80:20 to 50:50.
[0053] Solution B of compound (1) may be a solution in which compound (1) is dissolved in a solvent containing methanol and methyl isobutyl ketone, or may be a reaction solution obtained by reacting 3-hydroxy-2-naphthoic acid hydrazide, which is a precursor of compound (1), with methyl isobutyl ketone in a solvent. From the viewpoint of efficiently obtaining crystals, the reaction solution is preferred.
[0054] The concentration of compound (1) in solution B of compound (1) is not particularly limited, but may be, for example, 3% by mass or more, preferably 5% by mass or more. The concentration of compound (1) in solution B of compound (1) may be, for example, 40% by mass or less, preferably 30% by mass or less, from the viewpoint of efficiently obtaining crystals.
[0055] Furthermore, when solution B of compound (1) is a reaction liquid obtained by reacting 3-hydroxy-2-naphthoic acid hydrazide with methyl isobutyl ketone in a solvent, the concentration of 3-hydroxy-2-naphthoic acid hydrazide in the solution for obtaining the reaction liquid may be, from the viewpoint of efficiently obtaining crystals, for example, 2 mass% or more (e.g., 2.1 mass% or more), preferably 3 mass% or more (e.g., 3.5 mass% or more), and may be, for example, 30 mass% or less (e.g., 28.5 mass% or less), preferably 25 mass% or less (e.g., 21.5 mass% or less).
[0056] Solution B of compound (1) can be prepared, for example, by dissolving compound (1) in a solvent containing methanol and methyl isobutyl ketone with heating. The heating temperature is not particularly limited as long as it is a temperature at which compound (1) dissolves in the solvent containing methanol and methyl isobutyl ketone used, but may be, for example, 40° C. or higher, preferably 50° C. or higher, and may be near the boiling point of the methanol solvent, 64.7° C. The heating time is not particularly limited, and may be, for example, about 0.1 to 5 hours.
[0057] Furthermore, when solution B of compound (1) is a solution obtained by reacting a precursor of compound (1), the reaction temperature of the solution is not particularly limited and may be, for example, 50°C or higher (e.g., 60°C or higher, 70°C or higher, 80°C or higher, 90°C or higher, etc.), and a temperature at which the solvent can be refluxed is preferable. The reaction time is not particularly limited and may be, for example, 1 hour or more, 2 hours or more, 3 hours or more, etc.
[0058] In this production method, the solution B of compound (1) is cooled to obtain the crystal B of the present invention. The cooling rate is not particularly limited, but from the viewpoint of efficiently obtaining crystalline B, it may be, for example, 0.5 to 30° C. / min, preferably 0.5 to 20° C. / min, and more preferably 0.5 to 10° C. / min. The cooling temperature is not particularly limited as long as it is a temperature at which crystals precipitate, for example, −20° C. or higher, preferably 0° C. or higher, and may be, for example, lower than 40° C., preferably 30° C. or lower.
[0059] The aging may be carried out at the above cooling temperature, and the aging time may be appropriately set, for example, for 1 to 72 hours, preferably 1 to 48 hours, more preferably 1 to 24 hours, from the viewpoint of efficiently obtaining Crystal B of the present invention. The aging may be a procedure of stirring or leaving the mixture to stand without adding any other component.
[0060] The crystallization may be carried out by adding previously prepared crystals of compound (1) as seed crystals. The seed crystals may be prepared using the production method of the present invention.
[0061] The proportion of seed crystals added is not particularly limited, and may be 10% by mass or less (for example, 0.05 to 10% by mass, 0.1 to 8% by mass, 0.1 to 5% by mass) of the substrate (compound (1)).
[0062] The crystals obtained by the above production method may be isolated by a general solid-liquid separation operation (eg, filtration, centrifugation, etc.).
[0063] In addition, a crystal containing both crystal A and crystal B can be prepared, for example, in the above-mentioned method for producing crystal A, by stirring or aging for a relatively long period of time (e.g., 5 hours or more, 10 hours or more, 15 hours or more, etc.) after precipitation of crystal A. The stirring or aging temperature at this time is not particularly limited, but may be, for example, less than 50°C (e.g., 40°C or less, 30°C or less), preferably 20°C or less (e.g., 10°C or less), and may be, for example, -20°C or more, preferably 0°C or more.
[0064] The use of the crystals of the present invention obtained as described above is not particularly limited, but they may be suitably used, in particular, as an additive for rubber.
[0065] Therefore, the present invention includes a rubber additive containing the crystal of the present invention.
[0066] The rubber additive of the present invention may be used in any application, but may be particularly suitable for use in rubber compositions.
[0067] Therefore, the present invention includes a rubber composition containing the rubber additive of the present invention. Such a rubber composition can also be said to be a composition containing the crystal of the present invention (or the compound (1) containing the crystal of the present invention). The rubber composition of the present invention is only required to contain at least the crystals of the present invention, and may contain crystals other than the crystals of the present invention within the scope of the present invention. The proportion of the crystal of the present invention (crystal A, crystal B, or crystals A and B) in compound (1) is not particularly limited, and may be, for example, 30 mass% or more, 40 mass% or more, 50 mass% or more, 60 mass% or more, 70 mass% or more, 80 mass% or more, 90 mass% or more, etc.
[0068] [Rubber composition] The rubber composition may include a rubber component. The rubber component is not particularly limited, and examples thereof include diene rubbers (e.g., polybutadiene rubber, isoprene rubber, styrene butadiene rubber, styrene isoprene butadiene rubber, chloroprene rubber, acrylonitrile butadiene rubber, etc.), non-diene rubbers (e.g., ethylene propylene rubber, butyl rubber, etc.), etc. The rubber component may be either natural rubber or synthetic rubber. The rubber components may be used alone or in combination of two or more.
[0069] The rubber component contained in the rubber composition of the present invention preferably contains a diene rubber, and among these, it is particularly preferable to use natural rubber. The content of the diene rubber in the rubber component is not particularly limited, but from the viewpoint of maintaining excellent low heat buildup, it is preferably 80% by mass or more, and more preferably 90% by mass or more.
[0070] The rubber composition of the present invention may contain additives other than the rubber additive of the present invention. The other additives are not particularly limited and may be additives commonly used in the rubber industry. Examples of other additives include antioxidants (e.g., hydrazide compounds other than compound (1), phenol-based antioxidants, imidazole-based antioxidants, amine-based antioxidants, etc.), fillers {e.g., inorganic fillers [e.g., white fillers (e.g., silica, silicates, carbonates, metal oxides, etc.)], organic fillers (e.g., carbon black, etc.)}, vulcanizing agents (e.g., sulfur, etc.), process oils (e.g., paraffin-based process oils, naphthene-based process oils, aromatic process oils, etc.), vulcanization accelerators (e.g., thiazole-based vulcanization accelerators, sulfenamide-based vulcanization accelerators, etc.), vulcanization accelerator assistants [e.g., zinc oxide, fatty acids (e.g., stearic acid, etc.)], antioxidants, antiozonants, silane coupling agents, etc. The other additives may be used alone or in combination of two or more.
[0071] In the rubber composition, the proportion of the rubber additive of the present invention (or the crystal of the present invention, or compound (1) containing the crystal of the present invention) is not particularly limited, but from the viewpoints of low heat buildup, processability, and the like, it may be, for example, 0.05 to 30 parts by mass, preferably 0.05 to 10 parts by mass, and more preferably 0.05 to 5 parts by mass, per 100 parts by mass of the rubber component.
[0072] In addition, the proportion of the rubber additive of the present invention (or the crystal of the present invention, or compound (1) containing the crystal of the present invention) in the rubber composition is not particularly limited, but from the viewpoints of low heat buildup, processability, etc., it may be, for example, 0.02 to 18 mass%, preferably 0.02 to 6 mass%, and more preferably 0.02 to 3 mass% based on the total amount of the rubber composition.
[0073] The content of the rubber component of the present invention in the rubber composition of the present invention is appropriately set depending on the intended use of the rubber composition. For example, when the rubber composition is used for the purpose of maintaining the elasticity of the rubber without reducing it, the content of the rubber component in 100% by mass of the rubber composition is preferably 30 to 99% by mass, and more preferably 40 to 80% by mass.
[0074] (Filler) The rubber composition of the present invention usually contains a filler as another additive, in addition to the above-mentioned rubber component. By including a filler together with the rubber component and the crystals of the present invention, the dispersibility of the filler is improved, and performance such as strength and abrasion resistance can be maintained at a high level, while achieving excellent low heat build-up even when a filler is included.
[0075] Here, the content of the filler is not particularly limited, but is preferably 10 to 160 parts by mass, and more preferably 30 to 100 parts by mass, relative to 100 parts by mass of the rubber component. By optimizing the amount of the filler, better low heat buildup properties and abrasion resistance can be achieved, and when the content is 10 parts by mass or more, sufficient abrasion resistance can be obtained, and when the content is 160 parts by mass or less, deterioration of low heat buildup properties can be suppressed. In addition, in the rubber composition, the content of the filler is not particularly limited, but from the viewpoint of low heat generation, abrasion resistance, and the like, it may be, for example, 1,000 to 16,000 parts by mass, preferably 2,000 to 10,000 parts by mass, and more preferably 3,000 to 7,000 parts by mass (e.g., 4,000 to 6,000 parts by mass, etc.) per 100 parts by mass of the rubber additive of the present invention (or the crystal of the present invention, or compound (1) containing the crystal of the present invention).
[0076] The type of the filler is not particularly limited and may be any of the above-mentioned exemplified ones (e.g., carbon black, silica, etc.). Among them, it is preferable to contain carbon black from the viewpoint of realizing superior low heat generation properties and improving abrasion resistance. Examples of the carbon black include GPF, FEF, SRF, HAF, ISAF, IISAF, and SAF grade carbon black.
[0077] From the viewpoint of obtaining better abrasion resistance, the content of the carbon black is preferably 10 parts by mass or more, more preferably 30 parts by mass or more, and even more preferably 50 parts by mass or more, per 100 parts by mass of the rubber component. From the viewpoint of improving low heat build-up properties and processability while maintaining a high level of abrasion resistance, the content of the carbon black is preferably 160 parts by mass or less, more preferably 90 parts by mass or less, and even more preferably 70 parts by mass or less, per 100 parts by mass of the rubber component. Carbon black tends to deteriorate low heat buildup and processability, but the crystals of the present invention can achieve both low heat buildup and processability, so that a relatively large amount of carbon black can be contained. In addition, since the crystals of the present invention can contain a relatively large amount of carbon black, the fracture resistance of the rubber can be further improved.
[0078] The silica used as the filler is not particularly limited, and for example, wet silica, dry silica, colloidal silica, etc. can be used.
[0079] As the inorganic filler, for example, an inorganic compound represented by the following formula (I) can also be used. nM xSiO Y zH2O Formula (I) (In the formula, M is at least one selected from the group consisting of metals selected from the group consisting of Al, Mg, Ti, Ca, and Zr, oxides or hydroxides of these metals, and hydrates thereof, and carbonates of these metals; and n, x, y, and z are integers of 1 to 5, 0 to 10, 2 to 5, and 0 to 10, respectively.)
[0080] Inorganic compounds of the above formula (I) include alumina (Al2O3) such as γ-alumina and α-alumina; alumina monohydrate (Al2O3·H2O) such as boehmite and diaspore; aluminum hydroxide [Al(OH)3] such as gibbsite and bayerite; aluminum carbonate [Al2(CO3)3], magnesium hydroxide [Mg(OH)2], magnesium oxide (MgO), magnesium carbonate (MgCO3), talc (3MgO·4SiO2·H2O), attapulgite (5MgO·8SiO2·9H2O), titanium white (TiO2), titanium black (TiO 2n-1), calcium oxide (CaO), calcium hydroxide [Ca(OH)2], magnesium aluminum oxide (MgO·Al2O3), clay (Al2O3·2SiO2), kaolin (Al2O3·2SiO2·2H2O), pyrophyllite (Al2O3·4SiO2·H2O), bentonite (Al2O3·4SiO2·2H2O), aluminum silicate (Al2SiO5, Al4·3SiO4·5H2O, etc.), magnesium silicate (Mg2SiO4, MgS Examples of suitable crystalline aluminosilicates include calcium silicate (Ca2SiO4, etc.), calcium aluminium silicate (Al2O3·CaO·2SiO2, etc.), calcium magnesium silicate (CaMgSiO4), calcium carbonate (CaCO3), zirconium oxide (ZrO2), zirconium hydroxide [ZrO(OH)2·nH2O], zirconium carbonate [Zr(CO3)2], various zeolites, and crystalline aluminosilicates containing alkali metals or alkaline earth metals.
[0081] The method for producing the rubber composition is not particularly limited, and for example, each component contained in the rubber composition may be kneaded. The kneading method is not particularly limited, and a conventional method may be used, and a kneader (for example, a roll, an internal mixer, a Banbury mixer, etc.) may be used.
[0082] The order in which the components in the rubber composition are kneaded is not particularly limited. For example, all the components may be kneaded at once, or any one of the components may be kneaded in advance and then the remaining components may be kneaded.
[0083] The rubber composition of the present invention can be vulcanized to obtain a rubber. The vulcanization method is not particularly limited, and a conventional method may be used.
[0084] The use of the rubber is not particularly limited, but it may be particularly suitable for use in tires (for example, tread components, shoulder components, sidewall components, bead components, carcass components, etc.).
[0085] Therefore, the present invention also includes a tire (for example, a pneumatic tire) using the rubber composition. The method for manufacturing the tire is not particularly limited, and a conventional method may be used. EXAMPLES
[0086] The present invention will be specifically described below with reference to examples, but the present invention is not limited to these.
[0087] (Powder X-ray diffraction measurement) The crystal structure was measured using an X-ray diffraction measurement device (Rigaku Corporation, Ultima IV) with an X-ray tube of Cu, a tube voltage of 40 kV, a tube current of 40 mA, a sampling width of 0.02°, and a scan speed of 30° / min.
[0088] (Melting Point) The melting point of the crystals was calculated from the appearance temperature of an endothermic peak observed when the temperature was increased from 50°C to 170°C at a heating rate of 10°C / min under a nitrogen stream using a differential scanning calorimeter (DSC6200, manufactured by Seiko Instruments Inc.).
[0089] (Average particle size D 50 ) The average particle size of the crystals was measured using a laser diffraction particle size distribution analyzer "HELOS&RODOS" manufactured by Sympatec, and was calculated as the particle size at 50% of the sieve cumulative distribution, i.e., D 50 was measured.
[0090] (specific surface area) The specific surface area of the crystal was measured by the BET method using a "TriStar II" manufactured by Micromeritics.
[0091] Example 1 A reactor equipped with a Dean-Stark type reflux condenser and a stirrer was charged with 138 mL of methyl isobutyl ketone and 41 g of 3-hydroxy-2-naphthoic acid hydrazide (HNH) and heated to about 116°C (HNH concentration: 27.1% by mass), and heated under reflux for 3 hours while removing the distilled water. The reaction solution was cooled at a cooling rate of 1.7°C / min while stirring at 250 rpm to precipitate crystals at 80°C, and then immediately cooled to 5°C at 1.7°C / min. The precipitated crystals were filtered and dried under reduced pressure to obtain slightly brown crystals (crystals A).
[0092] The crystal A obtained as described above has a melting point of 157.4°C and a specific surface area of 0.7 m 2 / g, average particle size D 50 The diameter was 11.8 μm and the shape was columnar.
[0093] The results of powder X-ray diffraction measurement of Crystal A obtained in Example 1 are shown in FIG.
[0094] [Table 1]
[0095] As shown in FIG. 1 and Table 1, Crystal A obtained in Example 1 exhibited a peak with the maximum intensity at 6.9°. Furthermore, Crystal A obtained in Example 1 showed characteristic peaks at 6.9°, 14.5°, 15.5°, 16.1°, 19.1°, 23.4°, 24.1°, 27.9° and 28.8°.
[0096] Example 2 A reactor equipped with a Dean-Stark type reflux condenser and a stirrer was charged with 24 ml of methyl isobutyl ketone, 126 ml of methanol, and 33.0 g of 3-hydroxy-2-naphthoic acid hydrazide (HNH concentration: 21.7% by mass), heated to about 64°C, and heated under reflux for 6 hours. The reaction solution was cooled to 20°C at a cooling rate of 1.3°C / min, and after confirming that crystals had precipitated, the solution was aged at about 20°C for 12 hours. The precipitated crystals were filtered and dried under reduced pressure to obtain pale yellow crystals (crystals B).
[0097] The crystal B obtained as described above has a melting point of 160.1°C and a specific surface area of 0.9 m 2 / g, average particle size D 50 The diameter was 11.7 μm and the shape was columnar.
[0098] The results of powder X-ray diffraction measurement of Crystal B obtained in Example 2 are shown in FIG.
[0099] [Table 2]
[0100] As shown in FIG. 2 and Table 2, Crystal B obtained in Example 2 exhibited a peak with the maximum intensity at 25.2°. In addition, the crystals obtained in Example 2 showed characteristic peaks at 11.2°, 11.4°, 13.5°, 15.5°, 15.8°, 16.3°, 17.2°, 18.4°, 21.6°, 22.0°, 26.3° and 29.1°.
[0101] Example 3 138 mL of methyl isobutyl ketone and 41 g of 3-hydroxy-2-naphthoic acid hydrazide were charged into a reactor equipped with a Dean-Stark type reflux condenser and a stirrer, and the mixture was heated to about 116°C (HNH concentration: 27.1% by mass), and heated under reflux for 3 hours while removing the distilled water. The reaction liquid was cooled at a cooling rate of 1.7°C / min while stirring at 250 rpm, and after confirming that nuclei had precipitated at 80°C, it was cooled to 5°C at 1.7°C / min. The slurry was stirred for 15 hours under strong stirring conditions. After 15 hours, the crystals were filtered and dried under reduced pressure to obtain slightly brown crystals. The obtained crystals had a characteristic peak of crystal A and a characteristic peak of crystal B. In addition, the ratio of the peak intensity at 11.4° to the peak intensity at 6.9° in the obtained crystals was 8:92.
[0102] Rubber composition and method for producing rubber Each component shown in step (I) in Table 3 below was mixed in the ratio (parts by mass) and kneaded for 3 minutes in a Banbury mixer while adjusting the rotation speed so that the maximum temperature of the mixture would be 150°C. After curing until the temperature of the mixture reached 80°C or less, each component shown in step (II) in Table 3 was added in the ratio (parts by mass) and kneaded while adjusting the maximum temperature of the mixture to 110°C or less to produce each unvulcanized rubber composition. The obtained unvulcanized rubber composition was heated at 150°C for 30 minutes using a vulcanizing press to obtain each rubber.
[0103] Low heat generation (low heat generation index) test For each of the rubbers in Compounding Examples 1 and 2, the Tan δ value was measured using a viscoelasticity measuring device (manufactured by Metravib) under conditions of a temperature of 40° C., a dynamic strain of 5%, and a frequency of 15 Hz. In addition, for the rubber of Comparative Compounding Example 1, the Tan δ value was measured under the above conditions, and the Tan δ value was set to 100. The low heat build-up index was calculated based on the following formula and is shown in Table 3. Note that a smaller low heat build-up index value indicates lower heat build-up and smaller hysteresis loss. Formula: Low heat index = {(Tan δ value of each rubber in Compounding Example 1 or 2) / (Tan δ value of rubber in Comparative Compounding Example 1)}×100
[0104] Mooney Viscosity (Processability Index) Test The Mooney viscosity of the unvulcanized rubber compositions of Compounding Examples 1 and 2 was measured at 100°C using a Mooney viscometer. The Mooney viscosity of the unvulcanized rubber composition of Comparative Compounding Example 1 was measured in the same manner as above, and the Mooney viscosity was set to 100. The processability index was calculated based on the following formula and shown in Table 3. The smaller the processability index value, the better the processability and the better the productivity of the unvulcanized rubber composition. Formula: Processability index = {(Mooney viscosity of each unvulcanized rubber composition of Compounding Example 1 or 2) / (Mooney viscosity of the unvulcanized rubber composition of Comparative Compounding Example 1)} × 100
[0105] [Table 3] *1: NR: Natural rubber TSR20 *2: CB (carbon black); Cabot Corporation, N234 *3: Antioxidant (N-phenyl-N'-(1,3-dimethylbutyl)-p-phenylenediamine); manufactured by Kemai Chemical Co., Ltd. *4: Wax; Rhein Chemie Rheinau, Antilux 111 *5: Stearic acid; manufactured by Sichuan Tianyu Grease Co., Ltd. *6: Crystal A of 3-hydroxy-N'-(1,3-dimethylbutylidene)-2-naphthoic acid hydrazide obtained in Example 1 *7: Crystal B of 3-hydroxy-N'-(1,3-dimethylbutylidene)-2-naphthoic acid hydrazide obtained in Example 2 *8: Vulcanization accelerator (TBBS); N-(tert-butyl)-2-benzothiazole sulfenamide (Ouchi Shinko Chemical Industry Co., Ltd., Sancera-NS-G) *9: Sulfur; manufactured by Shanghai Jinghai Chemical Co., Ltd. *10: Zinc oxide; manufactured by Dalian Zinc Oxide Co., Ltd.
[0106] As the above results show, the rubbers of Compounding Example 1 and Compounding Example 2, which contained crystalline A or B, had excellent low heat buildup properties compared to the rubber of Comparative Compounding Example 1, which did not contain crystalline compound (1). In addition, the rubber of Compounding Example 1, which was prepared by adding Crystal A, was superior in terms of low heat buildup compared to the rubber of Compounding Example 2, which was prepared by adding Crystal B. Furthermore, in terms of processability, the unvulcanized rubber of Compounding Example 2, which was prepared by adding Crystal B, was superior to the unvulcanized rubber of Compounding Example 1, which was prepared by adding Crystal A. [Industrial Applicability]
[0107] The crystals of the present invention are extremely useful industrially since they can be used as a rubber additive capable of imparting low heat build-up to rubber components without significantly impairing processability.
Claims
1. A crystal of 3-hydroxy-N'-(1,3-dimethylbutylidene)-2-naphthoic acid hydrazide having a peak with maximum intensity at a diffraction angle (2θ) of 6.9±0.2° in a powder X-ray diffraction pattern.
2. A crystal of 3-hydroxy-N'-(1,3-dimethylbutylidene)-2-naphthoic acid hydrazide having characteristic peaks at diffraction angles (2θ) of at least 6.9±0.2°, 14.5±0.2°, 15.5±0.2°, 19.1±0.2°, 23.4±0.2°, 24.1±0.2°, 27.9±0.2° and 28.8±0.2° in a powder X-ray diffraction pattern.
3. A crystal of 3-hydroxy-N'-(1,3-dimethylbutylidene)-2-naphthoic acid hydrazide having a peak with maximum intensity at a diffraction angle (2θ) of 11.4±0.2° and / or 25.2±0.2° in a powder X-ray diffraction pattern.
4. A crystal of 3-hydroxy-N'-(1,3-dimethylbutylidene)-2-naphthoic acid hydrazide having characteristic peaks at diffraction angles (2θ) of at least 11.2±0.2°, 11.4±0.2°, 13.5±0.2°, 15.5±0.2°, 15.8±0.2°, 16.3±0.2°, 18.4±0.2°, 21.6±0.2°, 22.0±0.2°, 25.2±0.2° and 26.3±0.2° in a powder X-ray diffraction pattern.
5. A crystal comprising the crystal according to claim 1 or 2 and the crystal according to claim 3 or 4.
6. The crystal according to claim 5, wherein the ratio of the peak intensity at a diffraction angle (2θ) of 11.4±0.2° to the peak intensity at a diffraction angle (2θ) of 6.9±0.2° is 1:99 to 10:
90.
7. The crystal according to any one of claims 1 to 6, having a melting point of 151°C or higher.
8. A rubber additive comprising the crystal according to any one of claims 1 to 7.
9. A rubber composition comprising the crystals described in any one of claims 1 to 7.
10. A rubber composition comprising the crystals described in any one of claims 1 to 7 and a filler.
11. The rubber composition according to claim 10, wherein the filler content is 1,000 to 16,000 parts by mass per 100 parts by mass of the crystals.
12. A tire using the rubber composition according to any one of claims 9 to 11.
13. 3. The method for producing the crystal according to claim 1, comprising at least a step of forming crystal nuclei at 50° C. or higher in a solution containing 3-hydroxy-N'-(1,3-dimethylbutylidene)-2-naphthoic acid hydrazide.
14. 5. The method according to claim 3, further comprising at least a step of precipitating crystals from a solution of 3-hydroxy-N'-(1,3-dimethylbutylidene)-2-naphthoic acid hydrazide dissolved in a solvent containing methanol and methyl isobutyl ketone.
15. A method for improving low heat build-up and / or processability of rubber by using the crystals according to any one of claims 1 to 7.
Citation Information
Patent Citations
Pneumatic tire
JP1998330549A
Hydrazone derivative
JP1999292834A
Rubber composition and tire using the same
JP2019006845A
Rubber composition and pneumatic tires
WO1998044040A1
Rubber composition and tire
WO2019235526A1